Scaling Down the PGCM Scale to Assess Views on Ageing More Efficiently: Finding a New Alternative - Doseděl, Tomáš; Menšíková, Tereza; Vidovićová, Lucie (International journal of environmental research and public health, 2020)
The aim of the study is to present a new and efficient way of measuring the quality of life among older populations, with special attention to morale, positive outlook on life and ageing. The measure is based on the Philadelphia Geriatric Center Morale Scale (PGCM), originally consisting of 22 items. The growing numbers and proportions of older people among European populations has increased the need to obtain more reliable data on their needs, values, life experiences and overall quality of life. Using data from six surveys conducted in the Czech Republic, we have formulated a three-item positive outlook on life and ageing (POLA) scale. Our analyses are divided into three steps: (1) constructing the scale and testing its internal consistency; (2) testing the scale's external validity using mean comparisons and correlation coefficients; and (3) determining the factors affecting a positive outlook on later life, such as gender and education. We have confirmed that the three-item approach to measuring positive outlook on ageing as a part of morale is highly applicable to surveys, producing compelling results in assessing important quality-of-life sub-concepts, such as subjective health, subjective age, and loneliness.
Keywords: Psychometrics; Morale; Male; kvalita života; Aging; Quality of Life; Česká republika; Aged; mužské pohlaví; senioři; průzkumy a dotazníky; Czech Republic; senioři nad 80 let; lidé; ženské pohlaví; psychometrie; Humans; stárnutí; Aged, 80 and over; Female; Surveys and Questionnaires; morálka